The influence of post-2008 legislation on an acquisition that turned hostile: A South African case study - A. K. Biggs; C. B. Scheepers; M. M. Botha (South African Journal of Business Management, 2017)
Hostile acquisitions have a significant impact on managers and employees. The possibility of an acquisition creates uncertainty and when the acquisition turns hostile it is even more disruptive to the target organisation. Also, negative perceptions are often created in the media about the acquirer that influence employees' attitudes in the target organisation. Processes to successfully integrate the acquirer and target organisations are impacted by these antagonistic pre-acquisition circumstances. The Companies Act (no.71 of 2008) created opportunities for shareholders to hold an acquired company's management accountable for financial performance and the researchers set out to investigate how the intent of the new legislation played out in practice, by studying an acquisition that turned hostile. The single case study research methodology revealed the manoeuvring of both the acquiring and acquired companies which utilised the mechanisms available to them through the new legislative, regulatory and corporate governance landscapes. The researchers provide an extensive review of the relevant mergers and acquisitions' literature, as well as influence of the international legislative environment on the current local regulations. These regulations in turn, inform corporate governance and ultimately board behaviours. The researchers conducted qualitative interviews with key role players as well as legal and financial experts. The findings of the thematic analysis and triangulation process, informed a conceptual frame of three episodes.
Keywords: 650